2020
DOI: 10.1242/dmm.044040
|View full text |Cite
|
Sign up to set email alerts
|

Using systems medicine to identify a therapeutic agent with potential for repurposing in inflammatory bowel disease

Abstract: Objective: Inflammatory bowel diseases cause significant morbidity and mortality. Aberrant NF-κB signalling is strongly associated with these conditions, and several established drugs influence the NF-κB signalling network to exert their effect. This study aimed to identify drugs which alter NF-κB signalling and may be repositioned for use in inflammatory bowel disease.Design: The SysmedIBD consortium established a novel drug-repurposing pipeline based on a combination of in-silico drug discovery and biologica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…In our own earlier studies using the p65-DsRedxp/IκBα-eGFP double transgenic strain, we successfully showed that TNF induced p65 oscillations in murine intestinal-stem cell derived 3D organoid cultures [21]. In those experiments, we observed a first, synchronised wave of p65 nuclear translocation, followed by a second wave of partially synchronised translocation [21]. In the current study, we observed one wave of nuclear translocation in p65-DsRedxp/IκBα-eGFP macrophages upon LPS stimulation.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In our own earlier studies using the p65-DsRedxp/IκBα-eGFP double transgenic strain, we successfully showed that TNF induced p65 oscillations in murine intestinal-stem cell derived 3D organoid cultures [21]. In those experiments, we observed a first, synchronised wave of p65 nuclear translocation, followed by a second wave of partially synchronised translocation [21]. In the current study, we observed one wave of nuclear translocation in p65-DsRedxp/IκBα-eGFP macrophages upon LPS stimulation.…”
Section: Discussionmentioning
confidence: 96%
“…The p65-DsRedxp reporter mouse has previously been used for live fluorescence imaging of mouse intervertebral disc (IVD) explants, where it was shown that the RelA(p65) subunit translocated to nucleus of cells within the IVD following stimulation with IL-1β or TNF [20]. In our own earlier studies using the p65-DsRedxp/IκBα-eGFP double transgenic strain, we successfully showed that TNF induced p65 oscillations in murine intestinal-stem cell derived 3D organoid cultures [21]. In those experiments, we observed a first, synchronised wave of p65 nuclear translocation, followed by a second wave of partially synchronised translocation [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It takes data in multiple formats and automatically generates hypotheses about molecular mechanisms of studied pathologies, finds most promising drug targets and biomarkers and suggests drugs and active compounds as treatment candidates for the pathology. With the help of Genome Enhancer, several successful studies were performed including: identification of early diagnostic biomarkers of colorectal cancer ( 31 ); study of potential mechanisms of atherosclerosis ( 32 ); drug repurposing in IBD ( 33 ).…”
Section: Use Casesmentioning
confidence: 99%
“…This creates an imbalance in such databases towards human studies. Nevertheless, due to the lack of species specific pathway databases and especially due to the lack of experimental data to establish such databases, previous studies also used similar pathway databases to perform an upstream analysis in different animal species [129,210,211,[271][272][273]. However, the reduced applicability of such pathway databases to animal species increases the need to experimentally validate the findings proposed in my studies.…”
Section: Applying the Upstream Analysis To Non-human Speciesmentioning
confidence: 99%